Screening of Marine Algae of Oman Gulf for Biosorption of Cobalt - S.T Dalir; H Ghafourian; H Ghods; Y Asef; M.H Sahafipour; B.M Gharanjik; R Jalali-Rad (مجله علوم و فنون هسته‌ای, 2005)
Batch experiments were conducted to study the ability of marine algae collected from Oman Gulf, Iran, for sorption of cobalt from the metal nitrate solution. The biosorption experiments were performed using native and chemically pretreated sun-dried biomass of marine algae. Our finding indicated that MgCl2 pretreated Cystoseria indica, Sargassum glaucescens and Padina australis had more sorption capacities, while the CaCl2 pretreated ones showed lower capacity (comparing with non-treated native biomass). Also, a fall in the cobalt uptake capacity of Nizimuddinia zanardini, Gracilaria corticata, G. arcuata, Botryocladia leptopoda, Scinaia carnosa, Hypnea valentiae, Ulva fasciata and Codium sp. took place after treatment with chemicals, including CaCl2 (0.1 M), MgCl2 (0.1 M), CaCl2 (0.1 M)/HCl (pH 2) and HCl (0.1 M). Biosorption of cobalt was rapidly took place onto algal biosorbents and most of the sorbed metal ion was bound in the first minutes of contact. Uptake of cobalt was pH-dependent and the most cobalt removal occurred at pH 4. In our screening investigations, brown algae (Dictyota indica, N. zanardini, P. australis, S. glaucescens, and C. indica) removed cobalt most efficiently from aqueous solution, respectively. The capability of marine algae for separation of 60Co was tested and a high 60Co removal was demonstrated.